Assessment and evaluation of vitamin D levels in patients of moderate persistent asthma: a prospective study in rural hilly area - Sood, Vivek; Sood, Atal (International Journal of Advances in Medicine, 2016)
Background: The discovery of non-classical actions of vitamin D has opened new applications. Among these is its anti-inflammatory role in inflammatory diseases like asthma. Low levels of vitamin D have been associated with asthma severity and recurrent exacerbations. Emerging evidence suggests that vitamin D deficiency (VDD) is also associated with increased airway hyper-responsiveness, decreased pulmonary function and decreased response to standard anti-asthma therapy. Methods: In this prospective study, vitamin D levels were assessed in 50 consecutive consenting subjects of moderate persistent asthma diagnosed as per GINA guidelines. Levels were assessed in relation to exacerbations, seasonal variation in spring, rainy and winter season and lung function. Results: 62% subjects were having deficient levels of 25 (OH) Vitamin D (<20 ng/ml). None of study participant had sufficient levels of vitamin D. There was lack of seasonal effect due to variation in sun exposure in different seasons on levels of vitamin D. This study found no correlation (r=0.078) between levels of vitamin D and number of exacerbations in patients of asthma on regular treatment. In subjects groups having less and more than 3 exacerbations in nine months, difference of vitamin D levels and lung function was also statistically not significant. Conclusions: Findings of this study were consistent with HUNT study that concluded non association of low serum 25 (OH) D levels with airway obstruction. However, considerable variation in different study results with regard to seasonal, lung function and exacerbational variation underline the need for a meta-analysis in this field.